2016
DOI: 10.1002/ange.201601708
|View full text |Cite
|
Sign up to set email alerts
|

A Powerful CRISPR/Cas9‐Based Method for Targeted Transcriptional Activation

Abstract: Abstract:The targeted transcriptional activation of endogenous genes is an important tool for understanding physiological transcriptional networks, synthesizing genetic circuits, and inducing cellular phenotype changes. The CRISPR/Cas9 system has a great potential to achieve this purpose, however it has not yet succeeded to activate endogenous genes and induce cellular phenotype changes, efficiently. We herein show a powerful method for transcriptional activation by the CRISPR/Cas9-based system. Replacement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…refs. [51][52][53][54][55] ), our approach increases the number of genes that can be assayed in parallel while also overcoming many of the primary sources of variation in such models. Critically, this enables direct comparison of results across genes to discover convergent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…refs. [51][52][53][54][55] ), our approach increases the number of genes that can be assayed in parallel while also overcoming many of the primary sources of variation in such models. Critically, this enables direct comparison of results across genes to discover convergent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The unmethylated promoter in the targeted gene was cut out by two sgRNA‐Cas9 complexes and replaced with the microhomology arm (MHA)‐harboring DNA fragment, which contained the methylated promoter and two sgRNA‐target sites (1 T and 2 T) of both ends, using MMEJ‐dependent integration, thereby repressing the transcription of the targeted gene. Since a previous study demonstrated that the replacement of a methylated 700‐bp sequence upstream of the transcription start site (TSS) with an unmethylated sequence induces powerful transcriptional activation, 22 we considered the 700‐bp sequence upstream of the TSS to be crucial and, thus, targeted this region. The targeted region was amplified with PCR and then subjected to the insertion of DNA methylation with CpG methyltransferase (Donor DNA).…”
Section: Resultsmentioning
confidence: 99%
“…20,21 MMEJ requires a short homologous sequence (5-25 bp) for DNA double-strand break repair, resulting in precise integration into the targeted genomic loci. [22][23][24][25][26][27] MMEJ-mediated precise integration enables the development of a DNA methylation system by which an activated gene is silenced through the replacement of an unmethylated promoter with a methylated promoter. This system may be used to induce epigenetic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies have potential outcomes in plants as well. Reviews by Katayama et al (2016) and Piatek and Mahfouz (2017) provide an update on programmable transcriptional regulation.…”
Section: Targeted Transcriptional Regulationmentioning
confidence: 99%